Indigenous neonatal feeding and bathing practices of caregivers in Vhembe District, Limpopo province - Patience M. Tulelo; Fhumulani M. Mulaudzi (AOSIS, 2021)
Background: Caregivers are offered health information on neonatal care before they are discharged from the healthcare facilities after giving birth. However, they continue to feed and bath neonates in ways that are informed by indigenous traditions. Notably, these ways include the provision of supplementary feeds before 6 months and bathing the neonate as early as possible, which are practices that contradict the World Health Organization (WHO) recommendations of neonatal care. Objectives: This study aimed to explore and describe the indigenous neonatal feeding and bathing practices of caregivers in Vhembe District, Limpopo province. Setting: This study was conducted in Limpopo province at Vhembe District, Makhado Municipality. Methodology: A qualitative, explorative and descriptive enquiry was used to conduct 18 semi-structured individual interviews to explore and describe their indigenous neonatal feeding and bathing practices. Purposive and snowball sampling methods were used to select participants. Creswell's method of data analysis was used to analyse data. Ethical principles were maintained. Results: Two themes with sub-themes resulted from data analysis presenting indigenous neonatal feeding practices and indigenous neonatal bathing practices. Conclusion: This study revealed that caregivers use indigenous neonatal feeding and bathing practices across age groups and social standing. Younger mothers receive guidance from older women in their families or community. Midwives should know the indigenous neonatal feeding and bathing practices of the communities they serve to offer relevant culture-sensitive health education. Contributions: This study contributes to the creation of knowledge about indigenous neonatal care practices amongst mothers and caregivers.